2009
DOI: 10.1093/nar/gkp1160
|View full text |Cite
|
Sign up to set email alerts
|

The N-terminus of hTERT contains a DNA-binding domain and is required for telomerase activity and cellular immortalization

Abstract: Telomerase defers the onset of telomere damage-induced signaling and cellular senescence by adding DNA onto chromosome ends. The ability of telomerase to elongate single-stranded telomeric DNA depends on the reverse transcriptase domain of TERT, and also relies on protein:DNA contacts outside the active site. We purified the N-terminus of human TERT (hTEN) from Escherichia coli, and found that it binds DNA with a preference for telomeric sequence of a certain length and register. hTEN interacted with the C-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 89 publications
(155 reference statements)
5
60
1
Order By: Relevance
“…The requirement of residue R151 for interaction in our assay suggests that we are monitoring a different binding activity. We were unable to obtain a DNA binding affinity for the TEN domain using fluorescence anisotropy (data not shown), which is similar to results reported for both the Tetrahymena and human TEN domains using filter binding and electrophoretic mobility shift assays (Jacobs et al, 2006;Moriarty et al, 2005;Sealey et al, 2010). This result is not unexpected because a weak or rapid exchange between the DNA and the anchor-site would aid in translocation of the DNA substrate during telomeric synthesis.…”
Section: E76ksupporting
confidence: 67%
See 2 more Smart Citations
“…The requirement of residue R151 for interaction in our assay suggests that we are monitoring a different binding activity. We were unable to obtain a DNA binding affinity for the TEN domain using fluorescence anisotropy (data not shown), which is similar to results reported for both the Tetrahymena and human TEN domains using filter binding and electrophoretic mobility shift assays (Jacobs et al, 2006;Moriarty et al, 2005;Sealey et al, 2010). This result is not unexpected because a weak or rapid exchange between the DNA and the anchor-site would aid in translocation of the DNA substrate during telomeric synthesis.…”
Section: E76ksupporting
confidence: 67%
“…The anchor-site of human TERT has been shown to bind directly to a telomeric oligonucleotide through its N-terminal TEN domain in the absence of the RNA (Sealey et al, 2010;Wyatt et al, 2007;Wyatt et al, 2009). We developed a similar assay for the yeast TEN domain and found that MBP-Est2p TEN associates in a sequence-specific manner with telomeric DNA.…”
Section: E76kmentioning
confidence: 99%
See 1 more Smart Citation
“…By synthesizing the repetitive telomeric sequence using its RNA template, telomerase prevents cellular senescence in somatic cells (4). Moreover, human telomerase reverse transcriptase (hTERT), as the rate-limiting step in the activation of telomerase, is known to be an accurate measure of telomerase activity (TA).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, mouse (m)TERT levels also appear to diminish over time in primary cell cultures, in part, leading to cell senescence and cell death (1,6,10,14,18). Work with human primary cell lines has shown that ectopic expression of human TERT (hTERT) can lead to continued cell replication and hence, immortalization (21,31,37,39). More importantly, recent reports have shown immortalized hTERT cells remain differentiated, thus preserving the phenotypic properties that closely resemble in vivo characteristics (37,39).…”
Section: Epithelial; Polycysticmentioning
confidence: 99%